How Do Budget Level and Type of Incentives Influence Performance? - Putri, Caesar Marga; Susanti, Indah Wirantika (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 14 No 1 (2019)DO - 10.24843/JIAB.2019.v14.i01.p04, 2019)
This research experimentally compares the influence of budget-based contracts and social incentives on individual performance. This paper compares two different types of budget-based contracts, budget-linear and budget-fixed, along with social incentives on individual performance. Assigning individuals in different budget levels, 75% or 100%, to perform complex tasks will lead to different performance outputs. The results show that individual performance will be higher when they receive a budget-linear contract. Social incentives have a strong impact on both types of budget-based contracts. The result of the study on the influence of budget levels confirms previous research that higher budget levels will led to higher performance when compared with lower budget levels. Keywords: Budget-based incentive contracts, social incentives, budget level, task complexity, individual performance.